Analisis Kualitas Layanan Aplikasi Web Siuber Universitas Palangkaraya Menggunakan Model Iso 9126 Dan Pendekatan Kuesioner Pengguna - Widiatry, Widiatry; Ilham, Arbiyannoor (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study analyzes the software quality of the SIUBER academic information system using the ISO/IEC 9126 model. A quantitative descriptive method was applied through a Likert-scale questionnaire distributed to SIUBER users. Results reveal that Functionality and Usability received the highest scores, whereas Reliability recorded the lowest. The findings highlight the need for strengthening infrastructure stability, enhancing error recovery, and improving maintainability procedures to ensure optimal system performance.